2019
DOI: 10.3389/fnhum.2019.00186
|View full text |Cite
|
Sign up to set email alerts
|

An MRI Study of the Metabolic and Structural Abnormalities in Obsessive-Compulsive Disorder

Abstract: Obsessive-compulsive disorder (OCD) is a neuropsychiatric illness characterized by obsessions and/or compulsions. Its pathophysiology is still not well understood but it is known that the cortico-striatal-thalamic-cortical (CSTC) circuitry plays an important role. Here, we used a multi-method MRI approach combining proton magnetic resonance spectroscopy (H1-MRS) and diffusion tensor imaging (DTI) techniques to investigate both the metabolic and the microstructural white matter (WM) changes of the anterior cing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 76 publications
1
26
0
Order By: Relevance
“…Compared to HCs, the OCD group showed lower FA and higher RD values in the anterior cingulum, forceps minor, and ATR, which is in line with the classical cortico‐striato‐thalamo‐cortical (CSTC) circuit model of OCD 10,51‐53 and with prior research in this area. Specifically, reduced FA was previously reported in OCD patients within the anterior cingulum bundle, 7,9‐11,13,51,54 the forceps minor, 8,10,11,14,16‐18,20 and the ATR 21,55 . However, we also observed alterations outside the CSTC, including within the IFOF, which connects the frontal lobe to parieto‐occipito‐temporal regions.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Compared to HCs, the OCD group showed lower FA and higher RD values in the anterior cingulum, forceps minor, and ATR, which is in line with the classical cortico‐striato‐thalamo‐cortical (CSTC) circuit model of OCD 10,51‐53 and with prior research in this area. Specifically, reduced FA was previously reported in OCD patients within the anterior cingulum bundle, 7,9‐11,13,51,54 the forceps minor, 8,10,11,14,16‐18,20 and the ATR 21,55 . However, we also observed alterations outside the CSTC, including within the IFOF, which connects the frontal lobe to parieto‐occipito‐temporal regions.…”
Section: Discussionsupporting
confidence: 70%
“…To differentiate myelin‐related pathology from axonal damage, the component measures from which FA is derived can be studied: an increase in radial diffusivity (RD) may signify increased space between fibers suggesting demyelination or dysmyelination, 5 whereas a decrease in axial diffusivity (AD) may suggest axonal injury 6 . Although results are mixed, most previous dMRI studies have reported lower FA in patients with OCD as compared to healthy controls, most consistently in the cingulum bundle 7‐13 and corpus callosum 8,10,11,14‐18 . A small number of previous dMRI studies have also investigated RD and AD in OCD patients, which report higher RD values in the forceps major, 19 corpus callosum 14,20 and in widespread WM, 21 as well as no between‐group difference in AD, suggesting that decreased myelination rather than axonal degeneration may underlie WM pathology in OCD.…”
Section: Introductionmentioning
confidence: 99%
“…The flow chart of the identification and attrition of studies is provided in Figure 1. There were 20 TBSS studies included in the review (six studies recruiting child/adolescent patients (Ameis et al., 2016; Fitzgerald et al., 2014; Jayarajan et al., 2012; Rosso et al., 2014; Silk et al., 2013; Zarei et al., 2011) and 14 studies with adult patients (Benedetti et al., 2013; Bollettini et al., 2018; Bora et al., 2011; Fan, van den Heuvel, et al., 2015; Fontenelle et al., 2011; Gan et al., 2017; Hartmann et al., 2016; Hawco et al., 2017; Magioncalda et al., 2016; Nakamae et al., 2011; Salles Andrade et al., 2019; Spalletta et al., 2014; Yagi et al., 2017; Zhou et al., 2018)). Demographic information and clinical characteristics of participants in all 20 TBSS studies, as well as scanning parameters and main findings of FA analyses, are shown in Table 1 and Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…In the 20 studies, peak coordinates of FA alteration could not be retrieved after contacting the authors in three studies (Bora et al., 2011; Fontenelle et al., 2011; Hartmann et al., 2016), and one study conducted statistical comparisons with parametric t tests in Statistical Parametric Mapping software (Spalletta et al., 2014). Therefore, 16 studies met criteria to be included in the present meta‐analysis (six studies recruiting child/adolescent patients (Ameis et al., 2016; Fitzgerald et al., 2014; Jayarajan et al., 2012; Rosso et al., 2014; Silk et al., 2013; Zarei et al., 2011) and 10 studies with adult patients (Benedetti et al., 2013; Bollettini et al., 2018; Fan, van den Heuvel, et al., 2015; Gan et al., 2017; Hawco et al., 2017; Magioncalda et al., 2016; Nakamae et al., 2011; Salles Andrade et al., 2019; Yagi et al., 2017; Zhou et al., 2018). No study used overlapping patient samples.…”
Section: Resultsmentioning
confidence: 99%
“…A correlation between these findings was found in a combined structural MRI and fMRI study, which shows that the volume of the superior temporal sulcus is strongly correlated with functional connectivity between several brain regions that may form a neuro-network [177, 180] . The simultaneous 1H-MRS and DTI study, to investigate metabolic and white matter integrity alterations in OCD, found that the level of Glx to Cr ratio in the anterior cingulate cortex was higher in the OCD group than the healthy control group [181] . The study also found from DTI analysis that the FA values in the left cingulate bundle of the OCD group were significantly higher than the healthy controls.…”
Section: Multimodal Imaging Data Fusion: Diseasesmentioning
confidence: 99%